A new experimental adhesive system containing G-IEMA – physicochemical properties. Issue 4 (16th February 2019) - Vasconcelos e Cruz, Joana; Brito, José; Polido, Mário; Gonçalves, Luísa L.
Abstract: The ultimate goal of this study was the development of a new Bis-GMA-free dental adhesive system with improved adhesive properties. Instead of Bis-GMA, a dendritic macromer (G-IEMA), derived from 2-isocyanatoethyl methacrylate (IEMA), was used and its physicochemical properties were investigated. G-IEMA was synthesized and subsequently incorporated into an experimental adhesive (AE2) formulated without Bis-GMA. Double bond conversion (DBC), polymerization shrinkage (PS), water sorption (WS) and solubility (SL) were evaluated and results were compared with three other adhesives: – an experimental adhesive formulated with Bis-GMA (AE1); Scotchbond™ (SBU); and, Futurabond M+ ™ (FUT). Comparisons between adhesives for DBC, PS, WS and SL properties were performed using One-Way ANOVA and the Kruskal-Wallis test, at the 5% significance level. Statistical analysis of DBC data, using one-way ANOVA, revealed significant differences between adhesives ( p < .001). AE2 presented a significantly higher DBC than SBU ( p < .001) and FUT ( p = .004); no significant differences were observed between AE2 and AE1 ( p = .403) with 60 s of light-curing. Kruskal-Wallis test revealed no significant differences between adhesives ( p = .094) for PS. One-Way ANOVA showed no significant differences among adhesives for WS ( p = .213) and SL ( p = .175). In conclusion, G-IEMA-based adhesive AE2 presented comparable DBC, PS, WS and SL when compared to Bis-GMA-based adhesive AE1. The results obtained so far are promising, revealing that G-IEMA macromer might be a good substitute monomer to prepare Bis-GMA-free adhesive systems.